Knowledge, attitudes, and practices toward coronavirus disease 2019 among intensive care unit nurses in Hospital Universiti Sains Malaysia - Paul, Christie Lily Aida Pius (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
COVID-19 is an infectious disease caused by a newly discovered coronavirus at Wuhan, China on 2019. Hence, COVID-19 spreads across the world, the intensive care units (ICU) community must prepare for the challenges associated with this pandemic. A cross-sectional study has been conducted to assess the level of knowledge, attitudes and practices towards COVID-19 among ICU nurses in Hospital USM. This study also examined the correlation between level of knowledge, attitudes and practices toward COVID-19 among ICU nurses in Hospital USM. In addition, the study also examined the association between the socio-demographic data of respondents (age, gender, ethnicity, level of education and years in nursing practices) and the level of knowledge, attitudes and practices toward COVID-19. The Pearson Correlation Coefficient test was used to determine the correlation between the level of knowledge, attitudes and practices toward COVID-19 and to determine the association between the socio-demographic data of respondents (age, gender, ethnicity, level of education and years in nursing practices) and the level of knowledge, attitudes and practices toward COVID-19. A total 159 ICU nurse from ICU wards were recruited through purposive sampling. Data were collected from September 2021 to June 2022 using google form and analysed using SPSS version 26.0 for a window. Most of the respondents are female (88.7%). The results revealed that overall ICU nurses had a moderate level of knowledge towards COVID-19 , poor level of attitudes towards COVID-19 and good level of practices towards COVID-19. In addition, the findings were there was no significant association between level of knowledge and attitudes toward COVID-19 (p >0.05). Next, , the findings were there was no significant association between level of knowledge and practices toward COVID-19 (p >0.05). Meanwhile, there are significant association between level of attitude and level of practices (p= 0.001). The findings about the association between socio-demographic data of respondent (age, gender, ethnicity, level of education and years of nursing experiences) and the level of knowledge, attitudes and practices, there is significant only between age and knowledge as the p-value is 0.015. In conclusion, the level of knowledge and level of attitudes needs to increased and improved among ICU nurses so they will be able to delivery an excellent nursing care for COVID-19 patients.